Everyday enactments of humanity affirmations in post 1994 apartheid South Africa: a phronetic case study of being human as occupation and health - Kronenberg, Franciscus C W (Division of Occupational Therapy, 2019)
BACKGROUND: Two challenging concerns prompted this research. The first was post 1994 South African society’s historically entrenched dehumanized/ing condition. And the second was the ill-positionedness and ill-preparedness of occupational science accompanied occupational therapy to do something about it. Appropriate concepts to imagine and generate potentially humanizing and healing responses to violent-divided-wounded human relations were found to be lacking in both professional and public discourses. This study therefore conceived of and applied an original conceptual depiction of being human as ‘enacting humanity affirmations’. Two questions were asked: how are affirmations of our humanity enacted in everyday post 1994 apartheid South Africa? And, how is human occupation and health implicated in enacted humanity affirmations? Consistent with the values and power rationality nature of the first research question, this study was philosophically grounded in critical contemporary interpretations of Aristotle’s intellectual virtue phronesis, and the African relational ethic Ubuntu. METHODOLOGY: Case study was heuristically employed as both a method and the object of study, along with narrative enquiry to generate storied exemplars. Maximum variation sampling aimed for heterogeneity of participants. The stories which made up the instrumental collective case were selected on the criterion of encountering likely resonance within South Africa. Situated within a dehumanized/ing context, incidents-embedded instances of enacted humanity affirmations were handled as bounded systems. Information was gathered through and from multiple methods and sources, including narrative interviews, participants’ reflective journals, multiple documents review, and researcher’s notes. Data analysis proceeded from co-constructions of nine case narratives, an across-case thematic analysis, to thesis building. Together, these informed what this study’s case is about, what it is a case of, and for. Critical reflexivity was exercised by on-going attention to power issues in research interactions, and attempts to enact reciprocal gestures and shared decision-making. FINDINGS/DISCUSSION: This study is a case about everyday enacted humanity affirmations which present as remarkable, disrupting seemingly normalized systemic oppressive power dynamics. Three main themes emerged: 'spectra of relational agency possibilities'; 'embodied-embedded radical sens-abilities'; and, 'never forget how made to feel'. Interpretations and discussion of these findings make this study a case of revealing and disrupting the violent deceptive western(ized) ontological and epistemological premise that being human is a given for all. Redressing historically inflicted harm done to our humanity necessitates that the geo- and body-political epistemic positions, from where to generate applicable understandings of human occupation and health, are delinked from ‘whiteness’. CONCLUSION: This study builds a case for advancing an understanding of being human as occupation and health. Being human was found to be radically relational, and not a given but a political potentiality which manifests on a continuum of enacted harmful negations and salutogenic affirmations of our humanity. Also, cultivation of our being human as shared identity-integrity can advance humanity-health. These insights allow for potentially humanizing and healing societal responses to violent-divided-wounded human relations. This has implications for how occupational therapy and occupational science can position and prepare for being a humanizing and healing resource through research, practice, and education.